THE IDENTITY OF EUPLOEA TULLIOLUS GOODENOUGHI CARPENTER, 1942, A CROW BUTTERFLY (LEPIDOPTERA: NYMPHALIDAE, DANAINAE) FROM PAPUA NEW GUINEA - R.I. Vane-Wright (BRIN Publishing (Penerbit BRIN), 2019)
The nominal taxon Euploea tulliolus goodenoughi Carpenter, 1942, based on a unique crow butterfly collected on Goodenough Island in 1913, is shown to represent a small, aberrant female of the locally common Euploea leucostictos eustachius (Kirby, 1889). This new synonymy invalidates the only previous record of the Purple Crow, Euploea tulliolus (Fabricius, 1793), from the islands of Milne Bay Province, Papua New Guinea. However, two female Euploea tulliolus collected from islands in the Louisiade Archipelago during 2010 are reported here, constituting the first valid records of the Purple Crow from the Milne Bay islands.